Corrosion Inhibition Effects and Adsorption Characteristics of Ethanol Extract of King Bitters Root (Andrographis paniculata) on Mild Steel in Hydrochloric and Tetraoxosulphate (VI) Acid Media (Fountain Journal of Natural and Applied Sciences, 2013)
The corrosion inhibition performance of ethanol extract of Andrographis paniculata (King Bitter) root (EEAPR) on the corrosion of Mild Steel (MS) in 1.0 M HCl and H2SO4 acid solutions at 303K and elevated temperatures of 313, 323 and 333K was investigated and compared. The experimental work was performed by the use of weight loss and hydrogen evolution techniques. The results indicate that the extract inhibit the corrosion of mild steel in both acid media. However, the EEAPR exhibits higher maximum inhibition efficiency of 98.9 % in HCl than in H2SO4 (95.0 %) at 5.0 g/L. Inhibition efficiency was found to increase with increasing concentration of extract in both acid media but decreased with rise in temperature. Inhibition mechanism was deduced from the temperature dependence of the inhibition efficiency as well as from activation parameters that govern the process. Adsorption of extract on the MS sample in both acid media was found to obey the Langmuir adsorption isotherm. The phenomenon of physical adsorption is proposed from the obtained thermodynamic parameters.Keywords: Weight loss, Thermodynamics, Inhibition efficiency, Surface coverage, Hydrogen evolution.